Investigation of Factors Influencing Solenoid Valve Speed Response Characteristics of the Common Rail Injector - Yun Bai; Chengda Du; Qiang Sun; Shi Bu; Ao Wang (Machines)
The dynamic injection characteristics of high-pressure common rail fuel injection systems are determined by the speed response performance of the solenoid valve. A simulation model has been established for investigating the influence mechanism and change law of characteristic parameters on speed response characteristics of the solenoid valve. The speed response characteristics of the solenoid valve, including the average opening speed, the average closing speed, the maximum opening speed, and the maximum closing speed, caused by the changes of characteristic parameters such as pre-tightening force of the solenoid valve spring, mass of the solenoid valve moving parts, diameter of the outflow orifice, diameter of the inflow orifice, diameter of the control piston, and pressure in the common rail, have been studied. The correlation analysis of the influence factors is carried out by using the experimental design method based on the response surface model, and the correlation coefficients between each factor and the speed response characteristics of the solenoid valve are obtained. The results show that both single factors and interaction factors of the parameters are correlated with the speed response characteristics of the solenoid valve. The results of this paper can provide a theoretical reference for the design and optimization of the high-pressure common rail injector.